A stochastic volatility libor model and its robust calibration - Denis Belomestny; Stanley Matthew; John G. M. Schoenmakers (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
In this paper we propose a Libor model with a high-dimensional specially structured system of driving CIR volatility processes. A stable calibration prodecure which takes into account a given local correlation structure is presented. The calibration algorithm is FFT based, so fast and easy to implement.
Keywords: G12; 330; Libor modelling; stochastic volatility; CIR processes; calibration; LIBOR Market Modell; Zinstermingeschäft; Optionspreistheorie; Volatilität; Stochastischer Prozess; Robustes Verfahren; Theorie